A study of dupilumab in the treatment of adolescents with eczema. (2nd January 2020) - Cork, M.J.; Thaçi, D.; Eichenfield, L.F.; Arkwright, P.D.; Hultsch, T.; Davis, J.D.; Zhang, Y.; Zhu, X.; Chen, Z.; Li, M.; Ardeleanu, M.; Teper, A.; et al.
Summary: Atopic dermatitis (AD), also known as eczema, is characterized by red, oozy, and dry skin that can become cracked and infected. Intense itching, which can be very troublesome and can cause sleep disturbance, is the main complaint of patients with AD. AD often begins in childhood and affects 1 in 4 teenagers worldwide. For teenagers, the itchiness and appearance of AD skin can significantly reduce quality of life, but there are few effective treatment options for moderate‐to‐severe AD that are suitable for long‐term use. Dupilumab is a new drug that blocks key molecules that cause allergic conditions, such as AD. It has been shown to be effective in treating moderate‐to‐severe AD in adults and to be relatively safe for long‐term use. This study was conducted in multiple centres across Europe and Canada in 40 patients aged 12 to 17 who received treatment with dupilumab for up to a year. The researchers wanted to know whether dupilumab is effective and safe for treating AD with long‐term use in these patients. They also wanted to know how dupilumab is processed by the body in patients with AD in this age group. They found that treatment with dupilumab substantially improves the skin and symptoms of AD, including itching, in these younger patients, without causing any unexpected side effects. They also found that dupilumab is processed the same way in these younger patients as in adults. The improvements were maintained throughout the one year of treatment. The study results support the use of dupilumab in the continuous treatment of adolescents with moderate‐to‐severe AD. This summary relates to the study: Dupilumab in adolescents with uncontrolled moderate‐to‐severe atopic dermatitis: results from a phase IIa open‐label trial and subsequent phase III open‐label extension Abstract : Linked Article:  Cork et al. Br J Dermatol 2020; 182 :85–96